Controlling molecular condensation/diffusion of copper phthalocyanine by local electric field induced with scanning tunneling microscope tip. (22nd December 2017) - Nagaoka, Katsumi; Yaginuma, Shin; Nakayama, Tomonobu
Abstract: We have discovered the condensation/diffusion phenomena of copper phthalocyanine (CuPc) molecules controlled with a pulsed electric field induced by the scanning tunneling microscope tip. This behavior is not explained by the conventional induced dipole model. In order to understand the mechanism, we have measured the electronic structure of the molecule by tunneling spectroscopy and also performed theoretical calculations on molecular orbitals. These data clearly indicate that the molecule is positively charged owing to charge transfer to the substrate, and that hydrogen bonding exists between CuPc molecules, which makes the molecular island stable.